Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Pollution prediction of heating boiler plants based on data preprocessing and CNN-LSTM-attention model - Zhengda Lin; Jifeng Wang; Bingjie Yan; Zhe Fu; Liyan Liu; Dan Zhong; Xingwei Du; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Sheep milk protects while cow milk exacerbates DSS-induced colitis by differentially modulating the Akkermansia–short chain fatty acids–barrier axis - Naseer Ahmad; Zhongshi Zhu; Fu Xingwei; Li Danni; Wen Qinghua; Lei Zhang; Hao Yuan; Yuxuan Song (Food Bioscience, 2026)

Source apportionment and uncertainty assessment of nitrate and phosphate pollution in shallow groundwater in agricultural watersheds based on multi-isotope methods - Qingfei Chen; Chi Wang; Anqiang Chen; Rongyang Cui; Wanli Hu; Bin Fu; Cunzheng Jiang; Xingwei Chen; Dan Zhang (Groundwater for Sustainable Development, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Optimization of mechanical properties and finite element simulation analysis of hollow fiber membranes in gas-liquid membrane separation technology - Zhengda Lin; Yihe Wang; Zhe Fu; Dan Zhong; Xingwei Du; Jun Zhang (Desalination, 2025)

Seafloor Sediment Classification Using Small-Sample Multi-Beam Data Based on Convolutional Neural Networks - Haibo Ma; Xianghua Lai; Taojun Hu; Xiaoming Fu; Xingwei Zhang; Sheng Song (Journal of Marine Science and Engineering, 2025)
Accurate, rapid, and automatic seafloor sediment classification represents a crucial challenge in marine sediment research. To address this, our study proposes a seafloor sediment classification method integrating convolutional neural networks (CNNs) with small-sample multi-beam backscatter data. We implemented four CNN architectures for classification—LeNet, AlexNet, GoogLeNet, and VGG—all achieving an overall accuracy exceeding 92%. To overcome the scarcity of seafloor sediment acoustic image data, we applied a deep convolutional generative adversarial network (DCGAN) for data augmentation, incorporating a de-normalization and anti-normalization module into the original DCGAN framework. Through comparative analysis of the generated versus original datasets using visual inspection and grayscale co-occurrence matrix methods, we substantially enhanced the similarity between synthetic and authentic images. Subsequent model training using the augmented dataset demonstrated improved classification performance across all architectures: LeNet showed a 1.88% accuracy increase, AlexNet an increase of 1.06%, GoogLeNet an increase of 2.59%, and VGG16 achieved a 2.97% improvement.

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

Triplex visual detection of tobacco potyviruses using reverse transcription recombinase polymerase amplification assay combined with lateral flow dipstick - Tengzhi Xu; Xingwei Lin; Xiaolian Zhang; Yong Fu; Hao Luo; Chun Luo; Zhengduo Luo; Lei Lei; Meng-ao Jia (Crop Protection, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Novel ionic complex with flame retardancy and ultrastrong toughening effect on epoxy resin - Gaobo Lou; Qingqing Rao; Qing Li; Zhicheng Bai; Xingwei He; Youhua Xiao; Jinfeng Dai; Shenyuan Fu; Shengxiang Yang (Chemical Engineering Journal, 2023)

Light-enhanced transparent hydrogel for uric acid and glucose detection by four different analytical platforms - Wei Mao; Xingwei Cai; Ruirong Pan; Sheng Tang; Fu Yang; Yanjuan Cui; Jun Sun; Wei Shen (Analytica Chimica Acta, 2023)

Does pipelaying method affect the development of pipeline geohazards and maintenance cost? A case study of Zhongxian-Wuhan gas pipeline, China - Qinglu Deng; Min Fu; Xingwei Ren (Bulletin of Engineering Geology and the Environment, 2020)